2021
DOI: 10.18632/aging.202681
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and validation of an eight-gene metabolic–related prognostic signature model for lung adenocarcinoma

Abstract: In this study, we constructed an eight-gene metabolic related signature for LUAD. The eight-gene prognostic signature (including PLAUR, F2, UGT2B17, GNG7, IDO2, ST3GAL6, PIK3CG, and GLS2) exhibited a good prognostic value in the TCGA LUAD training dataset and testing dataset. In addition, the risk score based on the signature model was significantly correlated with immune cell infiltration and expression levels of immune markers in LUAD patients. LUAD cohorts from GEO were used to validate the model, indicatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Liang et al discovered a novel ferroptosisrelated prognostic gene signature for hepatocellular carcinoma (15). Several studies have identified prognostic gene signatures of LUAD involving glycolysis (16), metabolism (17), or immunity (18). These studies did not explain the role of ferroptosis in their models.…”
Section: Introductionmentioning
confidence: 99%
“…Liang et al discovered a novel ferroptosisrelated prognostic gene signature for hepatocellular carcinoma (15). Several studies have identified prognostic gene signatures of LUAD involving glycolysis (16), metabolism (17), or immunity (18). These studies did not explain the role of ferroptosis in their models.…”
Section: Introductionmentioning
confidence: 99%
“…In human hepatocellular carcinoma, Chinnadurai et al implicated IDO1 and PD-L1 as players in T cell suppression in this setting by investigating RNA expression of IDO/TDO and a set of B7 ligands. Lastly, in a retrospective study of non-small cell lung cancer (NSCLC), Mandarano et al report a correlation between elevated levels of IDO2 and poor prognosis, a finding recently confirmed by another group (9).…”
Section: Targeting Indoleamine 23-dioxygenases and Tryptophan Dioxygenase For Cancer Immunotherapymentioning
confidence: 85%
“…Lastly, in a retrospective study of non-small cell lung cancer (NSCLC), Mandarano et al. report a correlation between elevated levels of IDO2 and poor prognosis, a finding recently confirmed by another group ( 9 ).…”
mentioning
confidence: 85%
“…As a major component of the tumor microenvironment (TME), immune infiltration has been shown to contribute to tumor progression and the immunotherapeutic response ( Balkwill et al, 2012 ), and tumor-infiltrating immune cells, particularly T cells, are the cellular basis of immunotherapy. A better understanding of immune cells in the TME is critical to deciphering the mechanisms of immunotherapy, defining predictive biomarkers, and identifying new therapeutic targets ( Zhang and Zhang, 2020 ; Ma et al, 2021 ). In our GO analysis, most of the enriched functional terms were immune-related, and the same results were obtained by KEGG analysis.…”
Section: Discussionmentioning
confidence: 99%